Morphology induced enhanced photoconductivity of a phthalocyanine-based benzimidazole linked two-dimensional conjugated covalent organic polymer. (15th March 2022) - Duygulu, Ercan; Alev, Onur; Chumakov, Yurii; Öztürk, Zafer Ziya; Ayhan, Mehmet Menaf; Yuksel, Fatma
Abstract : A novel phthalocyanine-based benzimidazole linked conjugated covalent organic polymer (NiPc-COP1) has been synthesized with multiple randomly ordered crystalline morphologies. Abstract : A novel phthalocyanine-based benzimidazole linked conjugated covalent organic polymer (NiPc-COP1) has been synthesized with multiple randomly ordered crystalline morphologies. This unique alignment leads to significantly enhanced panchromatic light-absorption capability, and thus high photoconductivity with high photoresponse speed.